Veiled superheroes : Islam, feminism, and popular culture - Arjana, Sophia Rose (Lexington Books, 2018)
Veiled Superheroes: Islam, Feminism, and Popular Culture focuses on female Muslim superheroes in graphic narratives such as the comic Ms. Marvel, the animated television series Burka Avenger, and the webcomic Qahera.